Skip to main content

Theory and Modern Applications

Certain combinatoric Bernoulli polynomials and convolution sums of divisor functions

Abstract

It is known that certain convolution sums can be expressed as a combination of divisor functions and Bernoulli formula. One of the main goals in this paper is to establish combinatoric convolution sums for the divisor sums σ ˆ s (n)= d | n ( 1 ) n d 1 d s . Finally, we find a formula of certain combinatoric convolution sums and Bernoulli polynomials.

MSC:11A05, 33E99.

1 Introduction

The symbols and denote the set of natural numbers and the ring of integers, respectively. The Bernoulli polynomials B k (x), which are usually defined by the exponential generating function

t e x t e t 1 = k = 0 B k (x) t k k ! ,

play an important and quite mysterious role in mathematics and various fields like analysis, number theory and differential topology. The Bernoulli polynomials satisfy the following well-known identities:

j = 0 N j k = B k + 1 ( N + 1 ) B k + 1 ( 0 ) k + 1 ( k 1 ) = 1 k + 1 j = 0 k ( 1 ) j ( k + 1 j ) B j N k + 1 j .
(1.1)

The Bernoulli numbers B k are defined to be B k := B k (0). For nN, kZ, we define some divisor functions

σ k ( n ) : = d | n d k , σ k ( n ) : = d | n n d  odd d k , σ ˜ k ( n ) : = d | n ( 1 ) d 1 d k , σ ˆ k ( n ) : = d | n ( 1 ) n d 1 d k , σ k , l ( n ; 2 ) : = d | n d l ( mod 2 ) d k .

It is well known that σ k (n)= σ k (n) σ k ( n 2 ) and σ ˆ k (n)= σ k (n)2 σ k ( n 2 ) [[1], (1.13)]. The identity

k = 1 n 1 σ(k)σ(nk)= 5 12 σ 3 (n)+ ( 1 12 1 2 n ) σ(n)

for the basic convolution sum first appeared in a letter from Besge to Liouville in 1862 [2]. Hahn [[1], (4.8)] considered

36 m < n σ ˆ (m) σ ˆ (nm)={ 3 σ ˆ ( n ) + 3 σ ˜ 3 ( n ) if  n  is odd , 3 σ ˆ ( n ) 5 σ ˜ 3 ( n ) + 4 σ ˜ 3 ( n 2 ) if  n  is even .
(1.2)

For some of the history of the subject, and for a selection of these articles, we mention [3, 4] and [5], and especially [6, 7] and [8]. The study of convolution sums and their applications is classical, and they play an important role in number theory. In this paper, we investigate the combinatorial Bernoulli numbers and convolution sums. For k and n being positive integers, we show that the sum

j = 2 k ( 2 k + 1 2 j ) B 2 j σ ˆ 2 k + 1 2 j (n)

can be evaluated explicitly in terms of divisor functions and a combinatorial convolution sum. We prove the following.

Theorem 1 Let k, n be positive integers. Then

j = 2 k ( 2 k + 1 2 j ) B 2 j σ ˆ 2 k + 1 2 j ( n ) = ( 2 k + 1 ) σ 2 k + 1 ( n ) ( 2 k + 3 2 ) σ ˆ 2 k + 1 ( n ) ( k ( 2 k + 1 ) 6 ) σ ˆ 2 k 1 ( n ) ( 2 k + 1 ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ ˆ 2 k 2 s 1 ( m ) σ ˆ 2 s + 1 ( n m ) .

Remark 2 Let n be positive integers. In Theorem 1, replace k by 1, we find easily that

m = 1 n 1 σ ˆ (m) σ ˆ (nm)= 1 2 σ 3 (n) 5 12 σ ˆ 3 (n) 1 12 σ ˆ (n),
(1.3)

and in particular, if qN, p=2q+1, an odd prime integer, then

m = 1 q σ ˆ (m) σ ˆ (pm)= 1 6 q(q+1)(2q+1)= m = 1 q k 2 = 1 3 B 3 (q+1).
(1.4)

Equations (1.3) and (1.4) are in (1.2) and [[9], Corollary 2.4]. Using these combinatoric convolution sums, we obtain the following.

Theorem 3 If k is a positive integer, then

u + v + w = 2 k + 1 2 v 2 k 1 ( 2 k + 1 u , v , w ) B v ( 2 l + 1 ) w = B 2 k + 1 (l+1),

where ( 2 k + 1 u , v , w ) = ( 2 k + 1 ) ! u ! v ! w ! and l=1,2,3,4,5,6,7,8,9,10,11,12.

Thus, we can pose a general question regarding Bernoulli polynomials.

Question For all k,lN, does the identity

u + v + w = 2 k + 1 2 v 2 k 1 ( 2 k + 1 u , v , w ) B v ( 2 l + 1 ) w = B 2 k + 1 (l+1)hold?

The problem of convolution sums of the divisor function σ 1 (n) and the theory of Eisenstein series has recently attracted considerable interest with the emergence of quasimodular tools. In connection with the classical Jacobi theta and Euler functions, other aspects of the function σ 1 (n) are explored by Simsek in [10]. Finally, we prove the following.

Theorem 4 If a (≥2) and k are positive integers, then

  1. (i)
    s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 2 a 1 σ 2 k 2 s 1 , 1 ( m 2 ; 2 ) σ 2 s + 1 ( 2 a m ) = ( 1 2 ( 2 k + 1 ) ) B 2 k + 1 ( 2 a ) + ( 1 2 2 k 2 ( 2 k + 1 ) ) i = 1 a 1 B 2 k + 1 ( 2 i ) + 1 4 ( 2 ( 2 k + 1 ) a 1 2 2 k + 1 1 2 a + 1 + 1 ) ,
  2. (ii)
    s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 2 a 1 σ 2 k 2 s 1 , 0 ( m 2 ; 2 ) σ 2 s + 1 ( 2 a m ) = ( 1 + 2 2 k 2 ( 2 k + 1 ) ) i = 1 a 1 B 2 k + 1 ( 2 i ) + 1 4 ( 2 ( 2 k + 1 ) a 1 2 2 k + 1 1 ) + 1 2 ( 2 2 k ( a + 1 ) 2 2 k ( a + 1 ) 1 + 2 2 k a 1 1 2 2 k 1 ) + 2 a 2 ( 3 2 ( 2 k 1 ) ( a + 1 ) 2 ( 2 k 1 ) a + 1 2 2 k 1 1 ) + 2 a 1 1 4 ,
  3. (iii)
    s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 2 a 1 σ 2 k 2 s 1 ( m 2 ) σ 2 s + 1 ( 2 a m ) = ( 1 2 ( 2 k + 1 ) ) B 2 k + 1 ( 2 a ) + ( 1 ( 2 k + 1 ) ) i = 1 a 1 B 2 k + 1 ( 2 i ) + 1 2 ( 2 ( 2 k + 1 ) a 1 2 2 k + 1 1 ) + 1 2 ( 2 2 k ( a + 1 ) 2 2 k ( a + 1 ) 1 + 2 2 k a 1 1 2 2 k 1 ) + 2 a 2 ( 3 2 ( 2 k 1 ) ( a + 1 ) 2 ( 2 k 1 ) a + 1 2 2 k 1 1 ) .

2 Properties of convolution sums derived from divisor functions

Proposition 5 ([8])

Let k, n be positive integers. Then

j = 2 k ( 2 k + 1 2 j ) B 2 j σ 2 k + 1 2 j ( n ) = ( 2 k + 3 2 ) σ 2 k + 1 ( n ) ( 2 k + 1 ) ( k 6 n ) σ 2 k 1 ( n ) + ( 2 k + 1 ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 ( m ) σ 2 s + 1 ( n m ) .

Proposition 6 ([7, 11])

Let k, n be positive integers. Then

( i ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 ( m ) σ 2 s + 1 ( n m ) = 1 2 ( σ 2 k + 1 ( n ) n σ 2 k 1 ( n ) ) , ( ii ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n σ 2 k 2 s 1 ( 2 m 1 ) σ 2 s + 1 ( 2 n 2 m + 1 ) = 1 4 σ 2 k + 1 ( 2 n ) .

Proof of Theorem 1 Let k,nN. By Proposition 5 and Proposition 6, we obtain

T : = s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ ˆ 2 k 2 s 1 ( m ) σ ˆ 2 s + 1 ( n m ) = s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 ( σ 2 k 2 s 1 ( m ) 2 σ 2 k 2 s 1 ( m 2 ) ) × ( σ 2 s + 1 ( n m ) 2 σ 2 s + 1 ( n m 2 ) ) .

It is easily checked that

σ 2 k 2 s 1 ( m 2 ) σ 2 s + 1 ( n m ) + σ 2 k 2 s 1 ( m ) σ 2 s + 1 ( n m 2 ) = σ 2 k 2 s 1 ( m 2 ) σ 2 s + 1 ( n m 2 ) + σ 2 k 2 s 1 ( m ) σ 2 s + 1 ( n m ) + ( σ 2 k 2 s 1 ( m ) σ 2 k 2 s 1 ( m 2 ) ) ( σ 2 s + 1 ( n m ) σ 2 s + 1 ( n m 2 ) ) .

Thus,

T = s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 ( σ 2 k 2 s 1 ( m ) σ 2 s + 1 ( n m ) + 4 σ 2 k 2 s 1 ( m 2 ) σ 2 s + 1 ( n m 2 ) ) 2 s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 ( σ 2 k 2 s 1 ( m 2 ) σ 2 s + 1 ( n m 2 ) + σ 2 k 2 s + 1 ( m ) σ 2 s + 1 ( n m ) ) 2 s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 ( σ 2 k 2 s 1 ( m ) σ 2 k 2 s 1 ( m 2 ) ) × ( σ 2 s + 1 ( n m ) σ 2 s + 1 ( n m 2 ) ) = 2 s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 ( σ 2 k 2 s 1 ( m ) σ 2 k 2 s 1 ( m 2 ) ) ( σ 2 s + 1 ( n m ) σ 2 s + 1 ( n m 2 ) ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 ( σ 2 k 2 s 1 ( m ) σ 2 s + 1 ( n m ) 2 σ 2 k 2 s 1 ( m 2 ) σ 2 s + 1 ( n m 2 ) ) = 2 s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 ( m ) σ 2 s + 1 ( n m ) { ( 2 k + 3 4 k + 2 ) σ 2 k + 1 ( n ) + ( k 6 n ) σ 2 k 1 ( n ) + 1 2 k + 1 j = 2 k ( 2 k + 1 2 j ) B 2 j σ 2 k + 1 2 j ( n ) } + 2 { ( 2 k + 3 4 k + 2 ) σ 2 k + 1 ( n 2 ) + ( k 6 n 2 ) σ 2 k 1 ( n 2 ) + 1 2 k + 1 j = 2 k ( 2 k + 1 2 j ) B 2 j σ 2 k + 1 2 j ( n 2 ) } = ( σ 2 k + 1 ( n ) n σ 2 k 1 ( n ) ) ( 2 k + 3 4 k + 2 ) { σ 2 k + 1 ( n ) 2 σ 2 k + 1 ( n 2 ) } k 6 { σ 2 k 1 ( n ) 2 σ 2 k 1 ( n 2 ) } + n { σ 2 k 1 ( n ) σ 2 k 1 ( n 2 ) } 1 2 k + 1 j = 2 k ( 2 k + 1 2 j ) B 2 j { σ 2 k + 1 2 j ( n ) 2 σ 2 k + 1 2 j ( n 2 ) } = σ 2 k + 1 ( n ) ( 2 k + 3 4 k + 2 ) σ ˆ 2 k + 1 ( n ) k 6 σ ˆ 2 k 1 ( n ) 1 2 k + 1 j = 2 k ( 2 k + 1 2 j ) B 2 j σ ˆ 2 k + 1 2 j ( n ) .

This proves the theorem. □

Example 7 Let n be a positive integer. In Theorem 1, put k=2, we get

m = 1 n 1 σ ˆ (m) σ ˆ 3 (nm)= 1 8 σ 5 (n) 7 80 σ ˆ 5 (n) 1 24 σ ˆ 3 (n)+ 1 240 σ ˆ (n).

Corollary 8 Let k, n be positive integers. Then, we obtain

  1. (i)
    j = 2 k ( 2 k + 1 2 j ) B 2 j σ ˆ 2 k + 1 2 j ( 2 n ) = ( 2 k + 1 2 ) σ 2 k + 1 ( 2 n ) ( 2 k + 3 2 ) σ ˆ 2 k + 1 ( 2 n ) ( k ( 2 k + 1 ) 6 ) σ ˆ 2 k 1 ( 2 n ) ( 2 k + 1 ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ ˆ 2 k 2 s 1 ( 2 m ) σ ˆ 2 s + 1 ( 2 n 2 m ) ,
  2. (ii)
    j = 2 k ( 2 k + 1 2 j ) B 2 j { σ 2 k + 1 2 j ( n ) + σ 2 k + 1 2 j ( n 2 ) } = σ 2 k + 1 ( n ) 2 ( k + 1 ) σ 2 k + 1 ( n 2 ) ( 2 k + 1 ) ( k 3 n ) 6 σ 2 k 1 ( n ) ( 2 k + 1 ) ( k 6 n ) 6 σ 2 k 1 ( n 2 ) + 2 ( 2 k + 1 ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 ( m 2 ) σ 2 s + 1 ( n m ) ,
  3. (iii)
    j = 2 k ( 2 k + 1 2 j ) B 2 j σ 2 k + 1 2 j ( n ) = 2 k σ 2 k + 1 ( n ) k ( 2 k + 1 ) 6 σ 2 k 1 ( n ) n ( 2 k + 1 ) 2 σ ˆ 2 k 1 ( n ) 2 ( 2 k + 1 ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 ( m ) σ ˆ 2 s + 1 ( n m ) = 2 ( k + 1 ) σ 2 k + 1 ( n ) ( k 9 n ) ( 2 k + 1 ) 6 σ 2 k 1 ( n ) + n ( 2 k + 1 ) 2 σ 2 k 1 ( n 2 ) + 2 ( 2 k + 1 ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 ( m ) σ 2 s + 1 ( n m ) .

Proof (i) We note that

s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 ( 2 m ) σ 2 s + 1 ( n 2 m ) = s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 ( m ) σ 2 s + 1 ( n m ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 ( 2 m 1 ) σ 2 s + 1 ( n ( 2 m 1 ) ) .

(ii) and (iii) are applied in a similar way. □

3 Bernoulli polynomials and convolution sums

Proposition 9 ([12])

Let k, n be positive integers. Then

s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 2 2 k 2 s 1 σ 2 k 2 s 1 ( m / 4 ) σ 2 s + 1 ( n m ) = 1 4 σ 2 k + 1 ( n / 2 ) 1 4 ( σ 2 k ( n ) 2 2 k + 1 σ 2 k ( n / 2 ) 2 2 k σ 2 k ( n / 4 ) ) n 4 ( σ 2 k 1 ( n ) + 2 2 k σ 2 k 1 ( n / 4 ) ) + 1 2 σ 2 k , 1 ( n ; 2 ) + 2 2 k 1 2 k + 1 j = 0 2 k ( 2 k + 1 j ) B j σ 2 k + 1 j ( n / 2 ) + 1 2 ( 2 k + 1 ) j = 0 2 k ( 2 k + 1 j ) B j 2 2 k + 1 j σ 2 k + 1 j ( n / 4 ) + 1 2 ( 2 k + 1 ) j = 0 2 k ( 2 k + 1 j ) B j σ 2 k + 1 j , 1 ( n ; 2 ) 1 2 ( 2 k + 1 ) u + v + w = 2 k + 1 2 v 1 ( 2 k + 1 u , v , w ) B v σ w , 1 ( n ; 2 ) .

It is well known that σ 2 k 2 s 1 , 0 ( m 2 ;2)= 2 2 k 2 s 1 σ 2 k 2 s 1 ( m 4 ). Using Proposition 9, we get this lemma.

Lemma 10 Let k, n be positive integers. Then

  1. (i)
    s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 , 0 ( m 2 ; 2 ) σ 2 s + 1 ( n m ) = 1 4 σ 2 k + 1 ( n 2 ) + 1 4 ( 2 k + 1 ) σ 2 k + 1 , 0 ( n ; 2 ) + 1 2 ( 2 k + 1 ) σ 2 k + 1 , 0 ( n 2 ; 2 ) + 1 2 ( 2 k + 1 ) σ 2 k , 1 ( n ; 2 ) 1 4 σ 2 k ( n ) + 1 2 σ 2 k , 0 ( n ; 2 ) 1 4 σ 2 k , 0 ( n ; 2 ) + 1 4 σ 2 k , 1 ( n ; 2 ) n 4 σ 2 k 1 ( n ) + k 6 σ 2 k 1 , 0 ( n ; 2 ) + ( k 12 n 8 ) σ 2 k 1 , 0 ( n 2 ; 2 ) + k 12 σ 2 k 1 , 1 ( n ; 2 ) + 2 2 k 2 ( 2 k + 1 ) j = 2 k ( 2 k + 1 2 j ) B 2 j σ 2 k + 1 2 j ( n 2 ) + 1 2 ( 2 k + 1 ) j = 2 k ( 2 k + 1 2 j ) B 2 j σ 2 k + 1 2 j , 0 ( n 2 ; 2 ) + 1 2 ( 2 k + 1 ) j = 2 k ( 2 k + 1 2 j ) B 2 j σ 2 k + 1 2 j , 1 ( n ; 2 ) 1 2 ( 2 k + 1 ) u + v + w = 2 k + 1 2 v 1 ( 2 k + 1 u , v , w ) B v σ w , 1 ( n ; 2 ) ,
  2. (ii)
    s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 , 1 ( m 2 ; 2 ) σ 2 s + 1 ( n m ) = ( 1 2 ( 2 k + 1 ) ) σ 2 k + 1 ( n ) + ( k + 1 2 k + 1 ) σ 2 k + 1 ( n 2 ) + ( k 3 n 12 ) σ 2 k 1 ( n ) + ( k 6 n 12 ) σ 2 k 1 ( n 2 ) 1 4 σ 2 k + 1 ( n 2 ) ( 1 4 ( 2 k + 1 ) ) σ 2 k + 1 , 0 ( n ; 2 ) ( 1 2 ( 2 k + 1 ) ) σ 2 k + 1 , 0 ( n 2 ; 2 ) ( 1 2 ( 2 k + 1 ) ) σ 2 k , 1 ( n ; 2 ) + 1 4 σ 2 k ( n ) 1 2 σ 2 k , 0 ( n ; 2 ) + 1 4 σ 2 k , 0 ( n ; 2 ) 1 4 σ 2 k , 1 ( n ; 2 ) + n 4 σ 2 k 1 ( n ) k 6 σ 2 k 1 , 0 ( n ; 2 ) ( k 12 n 8 ) σ 2 k 1 , 0 ( n 2 ; 2 ) k 12 σ 2 k 1 , 1 ( n ; 2 ) 2 2 k 2 ( 2 k + 1 ) j = 2 k ( 2 k + 1 2 j ) B 2 j σ 2 k + 1 2 j ( n 2 ) 1 2 ( 2 k + 1 ) j = 2 k ( 2 k + 1 2 j ) B 2 j σ 2 k + 1 2 j , 0 ( n 2 ; 2 ) 1 2 ( 2 k + 1 ) j = 2 k ( 2 k + 1 2 j ) B 2 j σ 2 k + 1 2 j , 1 ( n ; 2 ) + 1 2 ( 2 k + 1 ) u + v + w = 2 k + 1 2 v 1 ( 2 k + 1 u , v , w ) B v σ w , 1 ( n ; 2 ) .

Remark 11 (i) Using Lemma 10, we obtain

u + v + w = 2 k + 1 2 v 1 ( 2 k + 1 u , v , w ) B v σ w , 1 ( n ; 2 ) = ( 2 k + 1 2 ) { σ 2 k + 1 ( n 2 ) σ 2 k ( n ) + 2 σ 2 k , 0 ( n ; 2 ) + σ 2 k , 0 ( n 2 ; 2 ) } ( n ( 2 k + 1 ) 2 ) { σ 2 k 1 ( n ) + 2 σ 2 k 1 , 0 ( n 2 ; 2 ) } + ( 2 k + 1 ) σ 2 k , 1 ( n ; 2 ) + 2 2 k j = 0 2 k ( 2 k + 1 j ) B j σ 2 k + 1 j ( n 2 ) + j = 0 2 k ( 2 k + 1 j ) B j σ 2 k + 1 j , 0 ( n 2 ; 2 ) + j = 0 2 k ( 2 k + 1 j ) B j σ 2 k + 1 j , 1 ( n ; 2 ) 2 ( 2 k + 1 ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 , 0 ( m 2 ; 2 ) σ 2 s + 1 ( n m ) = ( 2 k + 1 2 ) { σ 2 k + 1 ( n 2 ) 2 n σ 2 k 1 , 1 ( n 2 ; 2 ) + σ 2 k , 1 ( n 2 ; 2 ) } j = 0 2 k ( 2 k + 1 j ) B j σ 2 k + 1 j ( n ) + ( 2 2 k 1 ) j = 0 2 k ( 2 k + 1 j ) B j σ 2 k + 1 j ( n 2 ) + j = 0 2 k ( 2 k + 1 j ) B j σ 2 k + 1 j , 0 ( n 2 ; 2 ) + j = 0 2 k ( 2 k + 1 j ) B j σ 2 k + 1 j , 1 ( n ; 2 ) + 2 ( 2 k + 1 ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 , 1 ( m 2 ; 2 ) σ 2 s + 1 ( n m ) .
  1. (ii)

    If n is an odd integer, then

    u + v + w = 2 k + 1 2 v 1 ( 2 k + 1 u , v , w ) B v σ w , 1 ( n ; 2 ) = 2 ( 2 k + 1 ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 n 1 σ 2 k 2 s 1 , 1 ( m 2 ; 2 ) σ 2 s + 1 ( n m ) .
    (3.1)
  2. (iii)

    In (3.1), put k=1, we get

    u + v + w = 3 2 v 1 ( 3 u , v , w ) B v σ w , 1 (n;2)=12 m = 1 n 1 σ 1 , 1 ( m 2 ; 2 ) σ 1 (nm),

and thus,

m = 1 n 1 σ 1 , 1 ( m 2 ; 2 ) σ 1 (nm)= 1 24 ( σ 3 ( n ) σ 1 ( n ) ) .

In (3.1), replace k by 2, we find that

u + v + w = 5 2 v 1 ( 5 u , v , w ) B v σ w , 1 ( n ; 2 ) = 40 ( m = 1 n 1 σ 3 , 1 ( m 2 ; 2 ) σ 1 ( n m ) + m = 1 n 1 σ 1 , 1 ( m 2 ; 2 ) σ 3 ( n m ) ) ,

and thus,

m = 1 n 1 σ 3 , 1 ( m 2 ; 2 ) σ 1 ( n m ) + m = 1 n 1 σ 1 , 1 ( m 2 ; 2 ) σ 3 ( n m ) = 1 240 ( 3 σ 5 ( n ) 10 σ 3 ( n ) + 7 σ 1 ( n ) ) .

Proof of Theorem 3 If n=1, compare both sides of (3.1), we obtain

u + v + w = 2 k + 1 2 v 1 ( 2 k + 1 u , v , w ) B v =0.
(3.2)

If we put n=3 in (3.1), we obtain

u + v + w = 2 k + 1 2 v 1 ( 2 k + 1 u , v , w ) B v ( 1 + 3 w ) = u + v + w = 2 k + 1 2 v 1 ( 2 k + 1 u , v , w ) B v 3 w = 2 ( 2 k + 1 ) s = 0 k 1 ( 2 k 2 s + 1 ) .
(3.3)

From (3.1) and (3.3), we get

u + v + w = 2 k + 1 2 v 1 ( 2 k + 1 u , v , w ) B v 3 w =(2k+1) 2 2 k .
(3.4)

By combining (1.1) and (3.4), we obtain

u + v + w = 2 k + 1 2 v 1 ( 2 k + 1 u , v , w ) B v 3 w = 2 2 k B 2 k + 1 (2).

Others cases follow in a similar way. This completes the proof. □

Proof of Theorem 4 (i) If a is a positive integer, then

u + v + w = 2 k + 1 2 v 1 ( 2 k + 1 u , v , w ) B v σ w , 1 ( 2 a ; 2 ) = u + v + w = 2 k + 1 2 v 1 ( 2 k + 1 u , v , w ) B v =0

by (3.2). According to Remark 11(i), we deduce that

0 = 2 ( 2 k + 1 ) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 2 a 1 σ 2 k 2 s 1 , 1 ( m 2 ; 2 ) σ 2 s + 1 ( 2 a m ) j = 0 2 k ( 2 k + 1 j ) B j σ 2 k + 1 j ( 2 a ) + ( 2 2 k 1 ) j = 0 2 k ( 2 k + 1 j ) B j σ 2 k + 1 j ( 2 a 2 ) + j = 0 2 k ( 2 k + 1 j ) B j σ 2 k + 1 j , 0 ( 2 a 2 ; 2 ) ( 2 k + 1 2 ) { σ 2 k + 1 ( 2 a 2 ) 2 ( 2 a ) + 1 } .

If a=1, it is clearly evident. We suppose that a>1. We check that

j = 0 2 k ( 2 k + 1 j ) B j ( 2 a ) 2 k + 1 j = j = 0 2 k ( 2 k + 1 j ) ( 1 ) j B j ( 2 a ) 2 k + 1 j + 2 ( 2 k + 1 1 ) B 1 ( 2 a ) 2 k = ( 2 k + 1 ) j = 0 2 a j 2 k + 2 ( 2 k + 1 ) ( 1 2 ) ( 2 a ) 2 k = B 2 k + 1 ( 2 a )
(3.5)

by (1.1).

  1. (ii)

    and (iii) are applied in a similar way. □

Remark 12 If p is a prime integer, then

u + v + w = 2 k + 1 2 v 2 ( 2 k + 1 u , v , w ) B v p w =(2k+1) s = 0 k 1 ( 2 k 2 s + 1 ) m = 1 p 1 σ 2 k 2 s 1 , 1 ( m 2 ; 2 ) σ 2 s + 1 (pm)

by (3.1) and (3.2).

References

  1. Hahn H: Convolution sums of some functions on divisors. Rocky Mt. J. Math. 2007, 37(5):1593-1622. 10.1216/rmjm/1194275937

    Article  Google Scholar 

  2. Besge M: Extrait d’une lettre de M. Besge à M. Liouville. J. Math. Pures Appl. 1862, 7: 375-376.

    Google Scholar 

  3. Cheng N, Williams KS: Evaluation of some convolution sums involving the sum of divisors functions. Yokohama Math. J. 2005, 52: 39-57.

    MathSciNet  Google Scholar 

  4. Lahiri DB:On Ramanujan’s function τ(n) and the divisor function σ(n), I. Bull. Calcutta Math. Soc. 1946, 38: 193-206.

    MathSciNet  Google Scholar 

  5. Melfi G: On some modular identities. In Number Theory. de Gruyter, Berlin; 1998:371-382. (Eger, 1996)

    Google Scholar 

  6. Huard JG, Ou ZM, Spearman BK, Williams KS: Elementary evaluation of certain convolution sums involving divisor functions. II. Number Theory for the Millennium 2002, 229-274.

    Google Scholar 

  7. Kim D, Kim A, Sankaranarayanan A: Bernoulli numbers, convolution sums and congruences of coefficients for certain generating functions. J. Inequal. Appl. 2013., 2013: Article ID 225

    Google Scholar 

  8. Williams KS London Mathematical Society Student Texts 76. In Number Theory in the Spirit of Liouville. Cambridge University Press, Cambridge; 2011.

    Google Scholar 

  9. Kim D, Kim A, Kim M: A remark on algebraic curves derived from convolution sums. J. Inequal. Appl. 2013., 2013: Article ID 58

    Google Scholar 

  10. Simsek Y: Elliptic analogue of the Hardy sums related to elliptic Bernoulli functions. Gen. Math. 2007, 15(2-3):3-23.

    MathSciNet  Google Scholar 

  11. Kim D, Bayad A: Convolution identities for twisted Eisenstein series and twisted divisor functions. Fixed Point Theory Appl. 2013., 2013: Article ID 81

    Google Scholar 

  12. Cho, B, Kim, D, Park, H: Combinatorial convolution sums derived from divisor functions and Faulhaber sums (2013, submitted)

Download references

Author information

Authors and Affiliations

Authors

Corresponding author

Correspondence to Nazli Yildiz Ikikardes.

Additional information

Competing interests

The authors declare that they have no competing interests.

Authors’ contributions

All authors contributed equally and significantly in writing this article. All authors read and approved the final manuscript.

Rights and permissions

Open Access This article is distributed under the terms of the Creative Commons Attribution 2.0 International License (https://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Reprints and permissions

About this article

Cite this article

Kim, D., Yildiz Ikikardes, N. Certain combinatoric Bernoulli polynomials and convolution sums of divisor functions. Adv Differ Equ 2013, 310 (2013). https://doi.org/10.1186/1687-1847-2013-310

Download citation

  • Received:

  • Accepted:

  • Published:

  • DOI: https://doi.org/10.1186/1687-1847-2013-310

Keywords